Edukasi Aktifitas Fisik dan Latihan Terprogram untuk Mengurangi Penyakit Tidak Menular di Wilayah Rural Karanganyar - Pristianto, Arif; Samiyem, Samiyem; Rahman, Farid; Susilo, Taufik Eko; Naufal, Adnan Faris; Fatmarizka, Tiara (Abdi Geomedisains, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and heart disease are increasingly found in rural areas, including Karanganyar, which are experiencing a shift in lifestyle due to industrialization. Low public awareness of the importance of physical activity is one contributing factor. This community service aims to improve public knowledge and behavior through education and programmed physical exercise in the form of gymnastics and healthy walking. The implementation method includes initial observation, education using leaflet media, gymnastics training, and fun walking activities. This community service activity was successfully implemented and showed the enthusiasm of the community in participating in physical activity. The activity was attended by a total of 120 people, namely 60 participants for gymnastics and 60 participants for healthy walking. There was a significant increase in participant knowledge about the importance of physical activity in preventing non-communicable diseases, as evidenced by the increase in pre-test to post-test scores. Active community participation and support from local partners show that this community approach is effective in building awareness of healthy living and has the potential to be replicated in other rural areas.